Solve the equation 2 tan x - cot x + 1 = 0
Answers
Answered by
1
2 tan x - cot x + 1 = 0
![\cot(x) = \frac{1}{ \tan(x) } \\ \cot(x) = \frac{1}{ \tan(x) } \\](https://tex.z-dn.net/?f=+%5Ccot%28x%29+%3D+%5Cfrac%7B1%7D%7B+%5Ctan%28x%29+%7D+%5C%5C+)
put the value of cot X into the equation
![2 \tan(x) - \frac{1}{ \tan(x) } + 1 = 0 \\ \\ \frac{2 \: {tan}^{2}x - 1 + tan \: x }{tan \: x} = 0 \\ \\ 2 \: {tan}^{2}x - 1 + tan \: x = 0 \\ \\ 2 \: {tan}^{2}x + tan \: x - 1 = 0\\ 2 \tan(x) - \frac{1}{ \tan(x) } + 1 = 0 \\ \\ \frac{2 \: {tan}^{2}x - 1 + tan \: x }{tan \: x} = 0 \\ \\ 2 \: {tan}^{2}x - 1 + tan \: x = 0 \\ \\ 2 \: {tan}^{2}x + tan \: x - 1 = 0\\](https://tex.z-dn.net/?f=2+%5Ctan%28x%29+-+%5Cfrac%7B1%7D%7B+%5Ctan%28x%29+%7D+%2B+1+%3D+0+%5C%5C+%5C%5C+%5Cfrac%7B2+%5C%3A+%7Btan%7D%5E%7B2%7Dx+-+1+%2B+tan+%5C%3A+x+%7D%7Btan+%5C%3A+x%7D+%3D+0+%5C%5C+%5C%5C+2+%5C%3A+%7Btan%7D%5E%7B2%7Dx+-+1+%2B+tan+%5C%3A+x+%3D+0+%5C%5C+%5C%5C+2+%5C%3A+%7Btan%7D%5E%7B2%7Dx+%2B+tan+%5C%3A+x+-+1+%3D+0%5C%5C)
factorise the above equation
![2 {tan}^{2} x + 2 \: tanx - tan \: x - 1 = 0 \\ \\ 2 \: tanx(tan \: x + 1) - 1(tan \: x + 1) = 0 \\ \\ (2 \: tan \: x - 1)(tan \: x + 1) = 0 \\ \\ (tan \: x + 1) = 0 \\ \\ tan \: x = - 1 \\ \\ x = {tan}^{ - 1} ( - 1) \\ \\ x = \frac{ - \pi}{4} 2 {tan}^{2} x + 2 \: tanx - tan \: x - 1 = 0 \\ \\ 2 \: tanx(tan \: x + 1) - 1(tan \: x + 1) = 0 \\ \\ (2 \: tan \: x - 1)(tan \: x + 1) = 0 \\ \\ (tan \: x + 1) = 0 \\ \\ tan \: x = - 1 \\ \\ x = {tan}^{ - 1} ( - 1) \\ \\ x = \frac{ - \pi}{4}](https://tex.z-dn.net/?f=2+%7Btan%7D%5E%7B2%7D+x+%2B+2+%5C%3A+tanx+-+tan+%5C%3A+x+-+1+%3D+0+%5C%5C+%5C%5C+2+%5C%3A+tanx%28tan+%5C%3A+x+%2B+1%29+-+1%28tan+%5C%3A+x+%2B+1%29+%3D+0+%5C%5C+%5C%5C+%282+%5C%3A+tan+%5C%3A+x+-+1%29%28tan+%5C%3A+x+%2B+1%29+%3D+0+%5C%5C+%5C%5C+%28tan+%5C%3A+x+%2B+1%29+%3D+0+%5C%5C+%5C%5C+tan+%5C%3A+x+%3D+-+1+%5C%5C+%5C%5C+x+%3D+%7Btan%7D%5E%7B+-+1%7D+%28+-+1%29+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B+-+%5Cpi%7D%7B4%7D+)
for second value of x use another factor
![(2 \: tan \: x - 1) = 0 \\ \\ 2 \: tan \: x = 1 \\ \\ tan \: x = \frac{1}{2} \\ \\ x = {tan}^{ - 1} ( \frac{1}{2} )\\ (2 \: tan \: x - 1) = 0 \\ \\ 2 \: tan \: x = 1 \\ \\ tan \: x = \frac{1}{2} \\ \\ x = {tan}^{ - 1} ( \frac{1}{2} )\\](https://tex.z-dn.net/?f=%282+%5C%3A+tan+%5C%3A+x+-+1%29+%3D+0+%5C%5C+%5C%5C+2+%5C%3A+tan+%5C%3A+x+%3D+1+%5C%5C+%5C%5C+tan+%5C%3A+x+%3D+%5Cfrac%7B1%7D%7B2%7D+%5C%5C+%5C%5C+x+%3D+%7Btan%7D%5E%7B+-+1%7D+%28+%5Cfrac%7B1%7D%7B2%7D+%29%5C%5C)
by checking trigonometry functions table we can calculate the value x.
put the value of cot X into the equation
factorise the above equation
for second value of x use another factor
by checking trigonometry functions table we can calculate the value x.
Similar questions